2021
DOI: 10.1111/liv.14817
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib versus sorafenib in first‐line treatment of unresectable hepatocellular carcinoma: An inverse probability of treatment weighting analysis

Abstract: Purpose Data from common clinical practice were used to generate balanced cohorts of patients receiving either sorafenib or lenvatinib, for unresectable hepatocellular carcinoma, with the final aim to investigate their declared equivalence. Methods Clinical features of lenvatinib and sorafenib patients were balanced through inverse probability of treatment weighting (IPTW) methodology, which weights patients’ characteristics and measured outcomes of each patient in both treatment arms. Overall survival was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 12 publications
2
42
0
Order By: Relevance
“… 33 , 34 However, the resistance of sorafenib limits its long-term anticancereffect. The 1-year survival rate of unresectable HCC treated with sorafenib was less than 60%, and the median survival time is about 12 months, 35–37 which is far from satisfactory. The major neuronal isoform of RAF, BRAF and MEK pathways play a critical and central role in HCC escape from TKIs activity.…”
Section: Discussionmentioning
confidence: 96%
“… 33 , 34 However, the resistance of sorafenib limits its long-term anticancereffect. The 1-year survival rate of unresectable HCC treated with sorafenib was less than 60%, and the median survival time is about 12 months, 35–37 which is far from satisfactory. The major neuronal isoform of RAF, BRAF and MEK pathways play a critical and central role in HCC escape from TKIs activity.…”
Section: Discussionmentioning
confidence: 96%
“…23,25 Data confirmed recently by our group, where lenvatinib provided longer survival than sorafenib in patients previously submitted to TACE. 26 Furthermore, some data are emerging about the role of lenvatinib even in an earlier setting, i.e. before TACE; 27 indeed, systemic treatment may be preferred when intermediate-stage HCC is deemed TACEunsuitable, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…I read with interest the study by Casadei-Gardini et al who compared the effects of sorafenib and lenvatinib as first-line treatment of hepatocellular carcinoma (HCC) in the real-life setting, through inverse probability of treatment weighting (IPTW) methodology which weights patient characteristics and measured outcomes of each patient in both treatment arms. 1 They found that in the unadjusted cohort, lenvatinib did not show a survival advantage over sorafenib (HR: 0.85, 95% CI: 0.70-1.02). After IPTW adjustment, lenvatinib still not returned a survival advantage over sorafenib (HR: 0.82, 95% CI: 0.62-1.07) even in the presence of balanced baseline characteristics.…”
Section: Sorafenib and Lenvatinib As First-line Treatment Of Hepatocellular Carcinoma: A Still Controversial Comparisonmentioning
confidence: 97%